2000
DOI: 10.1097/00019514-200009010-00007
|View full text |Cite
|
Sign up to set email alerts
|

What Are Medicare Managed Care Plans Doing To Measure and Improve Quality of Care?

Abstract: To explore managed care plans' efforts to assess and improve quality of care for Medicare beneficiaries, the authors surveyed managed care plans with risk contracts for Medicare beneficiaries in 20 large metropolitan areas in January 1998. The survey inquired about: (1) the health plans' efforts to assess and improve quality of care for specific underuse, overuse, and misuse problems; (2) how the health plans assessed functional status of enrollees, and (3) the quality improvement program they believed had the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research from the late 1990s and early 2000s has qualitatively examined managed care efforts to promote quality for Medicaid patients enrolled in managed care plans (Becher, Halm, Lieberman, & Chassin, 2000; Cukor, Fairbrother, Tassi, Butts, & Friedman, 2002; Fairbrother, Friedman, Butts, Cukor, & Tassi, 2000; Landon, Schneider, Tobias, & Epstein, 2004; Landon, Tobias, & Epstein, 1998; Schneider, Landon, Tobias, & Epstein, 2004; Williams, Zaslavsky, & Cleary, 1999). Some studies have found that although managed care plans describe significant efforts to manage and improve care quality, knowledge of these efforts largely fails to reach providers and result in improved quality of care for patients (Cukor et al, 2002; Fairbrother et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Research from the late 1990s and early 2000s has qualitatively examined managed care efforts to promote quality for Medicaid patients enrolled in managed care plans (Becher, Halm, Lieberman, & Chassin, 2000; Cukor, Fairbrother, Tassi, Butts, & Friedman, 2002; Fairbrother, Friedman, Butts, Cukor, & Tassi, 2000; Landon, Schneider, Tobias, & Epstein, 2004; Landon, Tobias, & Epstein, 1998; Schneider, Landon, Tobias, & Epstein, 2004; Williams, Zaslavsky, & Cleary, 1999). Some studies have found that although managed care plans describe significant efforts to manage and improve care quality, knowledge of these efforts largely fails to reach providers and result in improved quality of care for patients (Cukor et al, 2002; Fairbrother et al, 2000).…”
Section: Introductionmentioning
confidence: 99%